2011
DOI: 10.1055/s-0030-1256110
|View full text |Cite
|
Sign up to set email alerts
|

Urgent endoscopy is associated with lower mortality in high-risk but not low-risk nonvariceal upper gastrointestinal bleeding

Abstract: Endoscopy within 13 h of presentation was associated with lower mortality in high-risk but not low-risk NVUGIB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
3
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(133 citation statements)
references
References 14 publications
4
117
3
9
Order By: Relevance
“…27 On the other hand, another study from Singapore demonstrated that endoscopy within 13 hours reduced mortality by 44% in patients with high-risk nonvariceal bleeding. 28 Youn et al 10 also found that if endoscopy was performed within 24 hours of admission, the mortality due to peptic ulcer bleeding would be reduced to 1.8% as compared to 6%7% in previous reports. However, the sample size of these studies was relatively small; fewer than 1000 patients were included for analysis.…”
Section: Discussionmentioning
confidence: 91%
“…27 On the other hand, another study from Singapore demonstrated that endoscopy within 13 hours reduced mortality by 44% in patients with high-risk nonvariceal bleeding. 28 Youn et al 10 also found that if endoscopy was performed within 24 hours of admission, the mortality due to peptic ulcer bleeding would be reduced to 1.8% as compared to 6%7% in previous reports. However, the sample size of these studies was relatively small; fewer than 1000 patients were included for analysis.…”
Section: Discussionmentioning
confidence: 91%
“…As mentioned above, a majority of these patients with a bloody aspirate had systolic blood pressure < 100 mm Hg and pulse > 100 beats / minute. A recent observational study also found a signifi cantly higher mortality in high-risk UGIB patients (Blatchford score ≥ 12) having endoscopy > 13 h aft er presentation (44 % ) than in those having earlier endoscopy (0 % , P < 0.001) ( 39 ). Multivariate analysis found that presentation-to-endoscopy time was the only variable signifi cantly associated with mortality.…”
Section: Patients With Ugib Should Generally Undergo Endoscopy Withinmentioning
confidence: 89%
“…Erythromycin has been also compared to nasogastric tube with gastric lavage and associated with satisfactory endoscopic conditions (38). Contrarily, the benefit of using metoclopramide has been questioned by some authors who report no improvement in the visualization of the gastric mucosa (39). Taking these results into account, erythromycin (single dose, 250 mg given 30-120 minutes prior to endoscopy) seems to be the preferred prokinetic and should be used when a large amount of blood is expected in the stomach (7).…”
Section: Pre-endoscopic Treatmentmentioning
confidence: 99%